The rotational spectrum of 17O2 up to the THz region. (January 2016) - Cazzoli, Gabriele; Kirsch, Till; Gauss, Jürgen; Puzzarini, Cristina
Abstract: The investigation of the pure rotational spectrum of the 17 O2 isotopic species of molecular oxygen has been extended with respect to previous investigations to the submillimeter-wave region, from 230 GHz up to 1.06 THz. The resulting spectroscopic parameters, which have an accuracy comparable to that of the constants obtained from an updated isotopic invariant fit involving data for three electronic states and six isotopologues [Yu et al. High resolution spectral analysis of oxygen. IV. Energy levels, partition sums, bandconstants, RKR potentials, Franck–Condon factors involving the X 3 Σ g −, a 1 Δ g, and b 1 Σ g + states. J Chem Phys 2014;141:174302/1–12], permit the prediction of the pure rotational transitions up to 2 THz with an estimated uncertainty not greater than 100 kHz. In the present study, high-level quantum-chemical calculations guided, supported, and complemented the determination of the hyperfine parameters of 17 O, with particular effort made in determining an accurate and reliable experimental value for the nuclear spin–rotation constant. A detailed discussion about the magnitude of the nuclear spin–rotation constant in the 17 O-containing O2 species for both the ground and the first excited electronic state is presented. Abstract : Highlights: Pure rotational spectrum of the 17 O 2 in the electronic ground state. Extension to the submillimeter-wave region: recording from 230 GHz up to 1.06 THz. A joint experimental–theoretical investigation: a complete characterization of the hyperfine parameters.